2021
DOI: 10.3389/fimmu.2021.791924
|View full text |Cite
|
Sign up to set email alerts
|

A Novel TGF-β Risk Score Predicts the Clinical Outcomes and Tumour Microenvironment Phenotypes in Bladder Cancer

Abstract: BackgroundThe TGF-β pathway plays critical roles in numerous malignancies. Nevertheless, its potential role in prognosis prediction and regulating tumour microenvironment (TME) characteristics require further elucidation in bladder cancer (BLCA).MethodsTGF-β-related genes were comprehensively summarized from several databases. The TCGA-BLCA cohort (training cohort) was downloaded from the Cancer Genome Atlas, and the independent validation cohorts were gathered from Xiangya Hospital (Xinagya cohort) and Gene E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…Finally, we collected many drug targets from the Drug Bank database. These therapeutic response related signatures or molecules were reported in our previous studies ( 16 , 17 ).…”
Section: Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…Finally, we collected many drug targets from the Drug Bank database. These therapeutic response related signatures or molecules were reported in our previous studies ( 16 , 17 ).…”
Section: Methodssupporting
confidence: 79%
“…Finally, we also associated GATA3 with the T-cell inflamed score, which represents the level of pre-existing cancer immunity ( 16 , 19 ). These immune characters were described in detail in our previous studies ( 16 , 17 ).…”
Section: Methodsmentioning
confidence: 92%
“…At present, TGF- β signaling pathway is widely utilized to predict the prognosis of various tumors, such as bladder cancer, hepatocellular carcinoma, and breast cancer [ 24 26 ]. Previous work has shown that TGF- β is essential for the tumorigenesis and invasion of head and neck squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Xiangya cohort: According to our previous study, the Xiangya cohort (GSE188715) comprised 57 BLCA samples sequenced on the BGISEQ-500 platform (BGI-Shenzhen, China) (13)(14)(15). Determination of pyroptosis gene sets: The keyword "pyroptosis" was searched in the GSEA public database (http://www.gsea-msigdb.org/gsea/msigdb/genesets.jsp).…”
Section: Data Sets Collection External Public Cohortsmentioning
confidence: 99%